When Lean Enterprises Collide: Competing through Confrontation. - Venkateswar, Sankaran; Boatsman, James R. (The Accounting Review, 1996)
Abstract Reviews the book `When Lean Enterprises Collide: Competing Through Confrontation,' by Robin Cooper.